100 things to know about history - Cowan, Laura (London. Usborne Publishing Ltd., 2018)
An eye-catching information book filled with one hundred interesting facts to learn from history: who really discovered America, who were the kings and queens we hear a lot about on TV, why America invaded Canada, and lots of other random facts to make history a fun subject!
U
b
b
Keywords: World History -- Juvenile Literature; History -- Juvenile Literature